MICROALBUMINURIA AS AN INDICATOR OF METABOLIC DISORDERS IN OBESITY CHILDREN - Goyibova, Nargiza; Garifulina, Lilya (Medical science of Uzbekistan, 2025)
The original article presents the results of a study of the relationship between microalbuminuria and carbohydrate and lipid metabolism parameters in children with obesity. The results of the study are recommended for widespread implementation in the practical activities of general practitioners and pediatricians. Research objective: To determine the relationship between microalbuminuria and carbohydrate and lipid metabolism parameters in children with obesity. Materials and methods: 55 children with primary exogenous constitutional obesity aged 7 to 18 years, as well as 20 children with normal body weight were studied. A set of anthropometric, clinical, and biochemical studies was conducted. Results of the study: a relationship was found between the degree of obesity and the severity of carbohydrate metabolism disorders and dyslipidemia in children, which was expressed in an increase in the level of cholesterol, triglycerides, LDL and a decrease in HDL, an increase in immunoreactive insulin and an increase in the IR HOMA R index. The study showed a relationship between the pathological level of urine albumin and the degree of pathology of carbohydrate and lipid metabolism, which indicates a significant contribution of the degree of metabolic disorders to the pathology of the functional capacity of the kidneys. Conclusion: in obesity, the kidneys are one of the first and main target organs most susceptible to damage, since they are the first to take on the function of correcting metabolism with an increase in the volume of adipose tissue. Thus, patients with excess accumulation of fat mass in the body should be considered as a group at very high risk of developing chronic kidney disease.